VIABILITY OF CANINE’S OVARIAN TISSUE AFTER NONEQUILIBRIUM CRYOCONSERVATION - Toishybek, D.; Nurkenov, T; Assanova, Y.; Salmenova, M.; Skvortsova, L.; Begmanova, M.; Bespalova, K.; Amirgaliyeva, A.; Perfilyeva, A.; Djansugurova, L.; Toishibekov, Ye. (Eurasian Journal of Applied Biotechnology, 2025)
Modern approaches to reproductive biotechnology include the development of effective methods for long-term storage of gametes and reproductive tissues of animals. One of the promising areas is cryopreservation of ovarian tissue, which allows preserving fertility, especially in rare and valuable species. However, the effectiveness of this technology directly depends on the type of cryoprotectant, freezing mode, cooling rate and storage method. Nonequilibrium cryopreservation is a method in which biological samples are exposed to liquid nitrogen vapor without strict software control of cooling. This approach allows for a simpler procedure but requires careful optimization of conditions to preserve tissue viability. The aim of this work is to evaluate the effect of various cryoprotectants and the altitude of the samples (4, 5 and 6 cm above the surface of liquid nitrogen) on the morphological preservation of follicles in the ovarian tissue of dogs after nonequilibrium cryopreservation. A study was conducted to investigate the effect of nonequilibrium cryopreservation in liquid nitrogen vapor on the morphofunctional state of ovarian tissue in dogs. Four cryoprotectors (dimethyl sulfoxide, ethylene glycol, propylene glycol, glycerol) and three temperature regimes (4 cm, 5 cm and 6 cm from the liquid nitrogen level) were used. After thawing, a histological analysis was performed to assess the degree of preservation of different types of follicles. It was found that the best viability indicators were observed when using 1.5 M dimethyl sulfoxide (4 and 6 cm), glycerol (4 cm) and propylene glycol (5 cm). The data obtained are important for the development of effective protocols for cryopreservation of ovarian tissue in dogs in order to preserve the gene pool and reproductive potential.